Impact of off-farm activities on technical efficiency: Evidence from maize producers of eastern Ethiopia - Musa Hasen Ahmed; Kumilachew Alamerie Melesse (Agricultural and Food Economics, 2018)
This article analyzes the impact of participation in off-farm activities on technical efficiency of maize production in eastern Ethiopia. We combined propensity score matching with a stochastic production frontier model that corrects sample selection bias resulting from unobserved factors that potentially affect both households' decision to participate in off-farm activities and technical efficiency scores that most previous studies do not account for. The probit model results indicate that sex of the household head, literacy of the spouse, agricultural cooperative membership, family size, and access to market information had significant effect on farmers' participation in off-farm activities. In the meantime, it was found that farmers who participated in off-farm activities have a significant technical efficiency gain compared with their non-participant counterparts.
Keywords: 330; Off-farm; Technical efficiency; Stochastic frontiers; PSM; Selection bias